Investigation of the Resistance of K-208 Glass with Optically Transparent Al–Si–N Nanocomposite Coatings to High-Speed Microparticle Impact; Russian Physics Journal; Vol. 62, iss. 3 - Bozhko I. A. Irina Aleksandrovna; Sungatulina E. V. Elena Vladimirovna; Kalashnikov M. P. Mark Petrovich; Fedorishcheva M. V. Marina Vladimirovna; Sergeev V. P. Viktor Petrovich; Khristenko Yu. F. Yury Fedorovich (2019, 2019)
Title screen